Engagement and relevance in the orchestra classroom through concert programming - Birkedal, Ellen L. (Kansas State University, 2022)
The purpose of this paper is to show the importance of relevance to music education and how it impacts the lives and engagement of students in a string orchestra program. Students engage in music as a regular part of their lives outside of the classroom, but oftentimes the musical experiences they have in the classroom do not connect with their lives outside of it. For the lesson plan shown in the video teaching demonstrations, the students first discussed which order to put certain musical selections in for their upcoming concert, then the students performed one of the pieces from that concert cycle. By allowing for greater student choice and input in the selected repertoire, and offering different styles and genres of music in every concert cycle, the experiences students have in the music classroom become relevant to their lives outside of the classroom. Throughout the course of my Masters’ Program, I have grown in pedagogical knowledge on the violin, viola, cello, and bass. My music reading skills, particularly in the alto clef have improved greatly, and I have been playing through each part before giving the music to students, thus making me more aware of nuances in the music and how it would impact the student’s performance of a piece. Perhaps the biggest area of growth that I have experienced during this process is a different approach to the way I structure and program my performances and the music that we perform. The structure that I used previously was in the format of three concerts per year. The first concert featured music from the Baroque, Classical, and Romantic time periods, the second featured Holiday and Contemporary music, and the third featured Pop and Movie music. The new concert structure that I have been using is one where each concert has a theme and all pieces fit the theme. This allows for multiple genres and styles of music to be played during each concert, which engages both the students and the audience, offers variety, and makes each concert relevant to everyone by playing what is familiar, and pushing the boundaries of experience to the unfamiliar.
Keywords: Concert programming; Orchestra classroom; Relevance; Engagement